Co-modulation of a circular form of PCDH11Y during neuroendocrine differentiation of prostate cancer - Pecoraro, Giovanni; Leone, Ilaria; Nuzzo, Silvia; Negueruela, Santiago; Smaldone, Giovanni; Buono, Lorena (Frontiers in Oncology, 2025)
IntroductionProstate cancer (PC) is a leading cause of cancer-related deaths among men, often progressing to castration-resistant prostate cancer (CRPC) after androgen deprivation therapy (ADT). A subset of CRPC evolves into treatment-emergent neuroendocrine prostate cancer (t-NEPC), an aggressive form characterized by poor prognosis. Currently, there is no reliable biomarker for early detection of t-NEPC. Circular RNAs (circRNAs) have emerged as potential biomarkers due to their stability and tissue-specific expression.MethodsIn this study, we investigated the circRNA landscape during neuroendocrine transdifferentiation (NED) of PC cells using the androgen-sensitive LNCaP and androgen-insensitive DU145 cell lines. To achieve that, we applied CirComPara2 pipeline to publicly available datasets to identify the differently expressed circRNAs in the LNCaP cell lines pre- and post-transdifferentiation. After that, validation and functional analysis by RNA-interference was applied to a selected circRNA to explore its role during NED. ResultsWe identified over 6,200 circRNAs, of which 33 were differentially expressed during NED. Among them, a novel circRNA, circPCDH11Y, was highly upregulated during the transition of LNCaP cells from an epithelial to neuroendocrine phenotype, while its levels remained unchanged in DU145 cells. Functional assays demonstrated that circPCDH11Y plays a role in regulating the expression of key neuroendocrine markers, including synaptophysin (SYP), neuron-specific enolase (ENO2), prostate-specific antigen (PSA), Brain-Specific Homeobox/POU Domain Protein 2 (BRN2) and the linear form of Protocadherin 11 Y-Linked (PCDH11Y). Silencing circPCDH11Y delayed the expression of SYP, ENO2 and PCDH11Y, while increasing PSA and BRN2 transcriptional levels, indicating its involvement in promoting neuroendocrine differentiation. Additionally, circPCDH11Y was detected in extracellular vesicles (EVs) secreted by LNCaP cells post-NED, suggesting its potential as a circulating biomarker. DiscussionThese findings highlight circPCDH11Y as a promising candidate for early detection of t-NEPC and provide new insights into the molecular mechanisms underlying prostate cancer progression. Further validation in clinical samples is required to establish its diagnostic and therapeutic potential, which could significantly improve the management of treatment-resistant prostate cancer.